IMPLEMENTASI MODEL PEMBELAJARAN TTW DAN PBL TERHADAP PEMECAHAN MASALAH SISWA DITINJAU DARI KEMANDIRIAN BELAJAR - Ahmad Taufik (JURNAL ILMIAH GLOBAL EDUCATION, 2020)
The purpose of this study was to determine the effect of the TTW and PBL learning models on solving mathematical problems in terms of learning independence, as well as the interaction between learning models and learning independence. This research is quasi-experimental (quasi-experimental research) carried out by involving all students of class IX SMPN in Central Lombok district as a population. The sample was selected using a stratified cluster random sampling technique. There are three schools out of 61 schools and two classes are taken in each school. Each class is grouped into experimental class I and experiment II. Experiment class I was taught using the TTW learning model and experiment II was taught using the PBL learning model. Data were collected using questionnaires and tests. Data were analyzed using the two way ANOVA method and followed by the Scheffe-test. The results showed that (1) the TTW and PBL learning models had a significant effect on problem-solving abilities; 2) the student's problem-solving ability in the TTW learning model is higher than the PBL learning model, 3) there is an interaction between the learning model and the student's learning independence on problem-solving abilities; 4) the problem-solving ability with the TTW learning model is higher than the problem-solving ability with the PBL learning model in each category of student independence